Evaluation of Vitamin D status in patients with Atopic Dermatitis (Eczema) in Sulaimani Province, Kurdistan region, Iraq - Hamad, Nasrin S.; Tofiq, Diary I. (Sulaimani Journal for Pure and Applied Sciences, 2019)
Skin inflammation or atopic Dermatitis (AD) is a long-lasting, inflammatory skin condition which generally develops in early life. The aetiology is a complex disorder with genetics, barrier function, immunity, and environmental factors all playing key roles in disease progression. Since vitamin D has immunomodulatory properties and immunologic systems assume a job in the pathogenesis of atopic eczema. The point of the investigation is to correspond vitamin D focuses in patients who have skin inflammation with the clinical and natural elements. Questionnaire population-based study 60 patients and 50 healthy volunteers (control) with age between 17-60 years were used in this study for about 3 months. The diagnosis has based the prevalence and morphology of hand eczema in a patient with atopic dermatitis in 2006 and the blood samples were collected from each patient before filling the questionnaire form, then the level of vitamin D (VD) was measured. The mean estimation of serum vitamin D in AD was greatly of lower than the normal value, and there was a substantial difference found in the mean estimations of vitamin D between AD patients (18.51) and the controls (23.38) with P value 0.001, there is a significant distinction between patients with mild eczema and those with severe eczema, which could lead to a significant increase in vitamin D deficiency as eczema worsens, while there was no significant association among VD subgroups with age, and gender in AD patients. The results from this study indicated that VD is the main factor in the development of AD and its supplementation may help ameliorate medical signs of the disease.
Keywords: Eczema; Atopic dermatitis,Severity; Vitamin D; Serum VD level